khatira THE ROLE OF LINGUACULTURAL ANALYSIS IN LITERARY TRANSLATION: THE ROLE OF LINGUACULTURAL ANALYSIS IN LITERARY TRANSLATION - Gaybullaeva, Khatira (Журнал иностранных языков и лингвистики, 2022)
In world translation studies, the comparative study of various works of art is gaining momentum. It is well known that translation is one of the most ancient forms of human activity, thanks to which we can clearly imagine all the details of the history of social development. Translation is a powerful weapon in the interests of international friendship, brotherhood and cooperation, as well as the expansion of economic, political, scientific, cultural and literary ties between nations. It accelerates the process of interaction and interaction between the literatures of different peoples. Thanks to the translated works, readers will enjoy the masterpieces of world literature. At the same time, translation is an important tool for accelerating the development of languages, increasing and improving the richness of vocabulary. This article analyzes the science of translation and its problems. Since no science can exist without taking into account and using the experience of the past, the work of predecessors in the relevant field, it is first necessary to use and generalize the data of the history of translation and translation thought, summing up the well-known result of the struggle of views and opinions on translation issues.